(untitled) (Academia Journal of Medicine, 2026)
Background: Ayurveda is a traditional Indian system of medicine that utilizes plant-based formulations for preventive and curative healthcare. Triphala, a tridoshic rasayana composed of Emblica officinalis, Terminalia chebula, and Terminalia bellerica, possesses well-documented antimicrobial properties attributed to tannins, flavonoids, phenols, and other polyphenolic compounds. Considering the growing concern of antimicrobial resistance, herbal alternatives are gaining attention in dental therapeutics. Aim: To comparatively evaluate the antimicrobial activity of Triphala hydrogel against Escherichia coli and Bacillus subtilis using amoxicillin as the standard control. Materials and Methods: An in vitro study was conducted using Triphala hydrogel formulations prepared at concentrations ranging from 2–10% w/v (F1–F5). Antimicrobial efficacy was assessed by agar diffusion method against Bacillus subtilis and Escherichia coli. Zones of inhibition (ZOI) were measured in millimetres and compared with amoxicillin as the positive control. Results: A concentration-dependent increase in antimicrobial activity was observed against both organisms. Against Bacillus subtilis, ZOI increased from 9.2 ± 0.5 mm (2% w/v) to 21.6 ± 0.9 mm (10% w/v). Against Escherichia coli, ZOI increased from 8.7 ± 0.5 mm to 19.4 ± 0.9 mm across the same concentration range. Amoxicillin demonstrated significantly higher inhibition zones (27.5 ± 1.2 mm and 26.8 ± 1.1 mm against Bacillus subtilis and Escherichia coli, respectively). Triphala formulations exhibited moderate yet significant antimicrobial activity, with the 10% w/v formulation showing optimal efficacy. Conclusion: Triphala hydrogel demonstrated dose-dependent antimicrobial activity against both gram-positive and gram-negative bacteria. Concentrations of 8–10% w/v appear optimal for therapeutic applications. Triphala-based hydrogels may serve as promising adjunctive herbal antimicrobial agents in dental care, particularly in the context of increasing antibiotic resistance.